2015
DOI: 10.1186/s12909-015-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of interprofessional education: a controlled trial to evaluate a programme for health professional students

Abstract: BackgroundCollaborative interprofessional practice is an important means of providing effective care to people with complex health problems. Interprofessional education (IPE) is assumed to enhance interprofessional practice despite challenges to demonstrate its efficacy. This study evaluated whether an IPE programme changed students’ attitudes to interprofessional teams and interprofessional learning, students’ self-reported effectiveness as a team member, and students’ perceived ability to manage long-term co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 36 publications
2
86
0
8
Order By: Relevance
“…Literature shows that exposure to classroom-based IPE experiences leads to a higher score on the RIPLS. [18][19][20][21][22][23] Our study suggests that these higher scores may be correlated with a higher learning effect of interprofessional collaboration, indicating that the translated scale can be used to inform us on attitudes towards interprofessional workplace learning. As interprofessional workplace learning is becoming an important aspect of the lifelong learning continuum, the call for undergraduate IPE as an amplifier of this dynamic becomes more pressing.…”
Section: Interpretation Of the Results In Relation To Existing Literamentioning
confidence: 99%
“…Literature shows that exposure to classroom-based IPE experiences leads to a higher score on the RIPLS. [18][19][20][21][22][23] Our study suggests that these higher scores may be correlated with a higher learning effect of interprofessional collaboration, indicating that the translated scale can be used to inform us on attitudes towards interprofessional workplace learning. As interprofessional workplace learning is becoming an important aspect of the lifelong learning continuum, the call for undergraduate IPE as an amplifier of this dynamic becomes more pressing.…”
Section: Interpretation Of the Results In Relation To Existing Literamentioning
confidence: 99%
“…Medves et al [22] pointed out that learners from different programmes need varied opportunities to communicate and work together, thus also training in outpatient primary care setting is valuable. Furthermore Darlow et al [23] found that even brief interventions improve attitudes for IPL.…”
Section: Discussionmentioning
confidence: 99%
“…The use of family cases helped the students to familiarize to public health state of the Finns, to public health programs and strategies and patient centred orientation as well as the meaning of shared responsibilities to improve public health. Darlow, Coleman, McKinlay, Donovan, Beckingsale, Gray, Neser, Perry, Stanley & Pullon (2015) resulted in short IP course improved attitudes of IP team working and collaboration towards patient centred care.…”
Section: Discussionmentioning
confidence: 99%